MSME Development Strategy Through Sharia Fintech Inclusion in Deli Serdang - Indrawan Lubis, Putri Salsabila; Nurbaiti; Ilhami Nasution, Muhammad lathief (Moneter: Jurnal Keuangan dan Perbankan, 2025)
This study focuses on evaluating the strategies employed to foster the growth of Micro, Small, and Medium Enterprises (MSMEs) through sharia fintech inclusion in Deli Serdang Regency. Using a descriptive qualitative approach and data collection techniques in the form of interviews and observations of MSME players, this study reveals the low level of literacy and adoption of sharia fintech even though this area has a majority Muslim population and has great potential in the development of Islamic finance. The results show This study concludes that the level of inclusion and literacy of Islamic fintech among MSMEs in Deli Serdang Regency remains relatively low. Although the potential for Islamic fintech use is significant, understanding of the basic concepts, principles of sharia, and benefits of Islamic fintech is not yet evenly distributed. Islamic fintech plays a crucial role in supporting transaction efficiency, financial record-keeping, and market expansion for MSMEs. However, obstacles such as low digital financial literacy and limited access to technology remain major challenges. The strategy for developing Islamic fintech-based MSMEs in Deli Serdang needs to encompass an educational approach, technological assistance, and cross-sector collaboration. Islamic financial literacy, strategic partnerships with Islamic fintech platforms, optimization of Islamic social funds (ZISWAF), and the development of a halal ecosystem are strategic steps that require comprehensive and sustainable development.